Information Retrieval Technology 9th Asia Information Retrieval Societies Conference, AIRS 2013, Singapore, December 9-11, 2013, Proceedings - Banchs, Rafael.; Banchs, Rafael.; Silvestri, Fabrizio.; Silvestri, Fabrizio.; Liu, Tie-Yan.; Liu, Tie-Yan.; Zhang, Min.; Zhang, Min.; Gao, Sheng.; Gao, Sheng.; Lang, Jun.; Lang, Jun. (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2013)
This book constitutes the refereed proceedings of the 9th Information Retrieval Societies Conference, AIRS 2013, held in Singapore, in December 2013. The 27 full papers and 18 poster presentations included in this volume were carefully reviewed and selected from 109 submissions. They are organized in the following topical sections: IR theory, modeling and query processing; clustering, classification and detection; natural language processing for IR; social networks, user-centered studies and personalization; and applications.